DEVELOPING PROBLEM-BASED LEARNING WORKSHEETS TO ENHANCE PROBLEM-SOLVING SKILLS IN NUMBER PATTERNS FOR JUNIOR HIGH SCHOOL STUDENTS - Ismalyanti, Rima; Asmar, Ali; Fauzan, Ahmad; Arnawa, I Made (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to design a student worksheet grounded in the Problem-Based Learning (PBL) approach that meets the criteria of validity, practicality, and effectiveness to enhance junior high school students' mathematical problem-solving skills in the topic of number patterns. Employing the Plomp development framework, the research followed three sequential phases: preliminary investigation, design, and assessment. The needs analysis identified limitations in conventional teaching practices and inadequate learning resources, which often hinder student understanding. The developed worksheet integrates the five essential stages of PBL and was validated through expert evaluation, limited trials, and broader implementation. Results demonstrated that the worksheet was highly valid with an average expert score of 3.71. Practicality testing showed strong user engagement and clarity, with a score of 83.8%, while effectiveness was confirmed by a 91.4% student mastery rate in mathematical problem-solving based on Polya’s stages. These findings suggest that the PBL-based worksheet significantly contributes to students' cognitive development and offers a viable instructional tool for mathematics education.